Polymorphism in 5′ untranslated region of heat‐shock protein 70 gene as marker of post‐partum anoestrus in Murrah buffaloes. (12th March 2017) - Kumar, R; Ghosh, M; Kumar, N; Balhara, AK; Gupta, M; Sharma, RK; Singh, I
Contents: The enormous production potential of buffaloes has never been accomplished due to various reproductive insufficiencies. Among them, post‐partum anoestrus, a multifactorial disorder, is predominant but any genetic association is yet to be established. This study focused to identify novel polymorphisms in heat‐shock protein 70 ( HSP70 ) gene and its possible association with post‐partum anoestrus in Murrah buffaloes. A 579‐bp fragment from 5′ untranslated region of HSP70 gene was amplified by polymerase chain reaction from blood genomic DNA of 614 animals maintained under similar management conditions. In phase‐I experiment, custom sequencing and restriction enzyme (RE) digestion of the amplified fragment were performed in 40 buffaloes with similar post‐partum oestrous conditions over previous consecutive three or more gestations—20 animals each showing post‐partum anoestrus (>120 days after parturition) and normal cyclicity (<65 days after parturition). While in phase‐II experiment, herd screening by RE analysis was performed in remaining 574 animals. Four transversions at T‐75G, C+31G, T+38G and C+97A and three transition mutations at T‐153C, T+33C and A+44G positions were observed. Polymorphism at T+38G site revealed significant ( p  < .05) variation, where homozygous G was present only in post‐partum anoestrous animals while nucleotide T was present randomly in both groups of phase‐I animals whereas phase‐II experiments revealed homozygous G in 55 animals. Regression analysis in relation to average post‐partum interval against genotypic frequencies at T+38G also depicted significant association. HSP70 gene polymorphism at T+38G position can therefore be used as genetic marker for excluding probable post‐partum anoestrous buffaloes from herd for breeding programmes.